Determination of Abraham model solute descriptors for 4-tert-butylbenzoic acid from experimental solubility data in organic mono-solvents. (4th July 2019) - Hart, Erin; Lee, Grace; Qian, Ellen; Jodray, Megan; Barrera, Maribel; Fischer, Rachel; Che, Melanie; Liu, Yuqing; Zha, Olivia; Woods, Delani; Acree, William E.; Abraham, Michael H.
ABSTRACT: Mole fraction solubilities are determined at 298 K for 4- tert -butylbenzoic acid dissolved in 11 different alcohols (1-butanol, 2-butanol, ethanol, 1-heptanol, 1-hexanol, 2-methyl-1-propanol, 2-methyl-2-propanol, 3-methyl-1-butanol, 1-pentanol, 1-propanol, and 2-propanol), in three different alkoxyalcohols (2-butoxyethanol, 2-ethoxyethanol, and 2-methoxyethanol), in five different alkyl alkanoates (butyl acetate, ethyl acetate, methyl acetate, pentyl acetate, and propyl acetate), in one cyclic ether (1, 4-dioxane) and in two different alkanenitriles (acetonitrile and propanenitrile). Results of the experimental solubilities are used to calculate Abraham model solute descriptors for the monomeric form of 4- tert -butylbenzoic acid. The calculated Abraham model solute descriptors back-calculated the observed solubility data to within 0.079 log units.